Limnology Some New Aspects of Inland Water Ecology - Gökçe, Didem (IntechOpen, 2019)
Anthropogenic influences, such as changing climatic conditions, domestic and industrial pollution, eutrophication, and salinization, have great impacts on freshwater systems. Nutrient cycling in freshwater ecosystems, population dynamics and community structure, water quality, sustainability, and management of ecosystem stability are increasingly important. Establishing a management strategy using a multidisciplinary approach ensures the sustainability of water resources. The present and future work being done in the field of limnology is necessary for preserving and protecting our freshwater ecosystems. In this respect, limnology is a rapidly developing science that has many significant aspects. The scope of this book covers all aspects of freshwater environment studies, from physical and chemical to biological limnology. This book provides useful information on basic, experimental, and applied limnology to researchers and decision makers.